Community Empowerment and Village Government (BPMPD) Strategy in Improving Village Government Capacity in Sumbawa District - Awanta Mutmainnah; Ni G.A. Liga Ambarwati (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
This research aimed to analyze the aparraturs capacity in village government and thestrategy of Badan Pemberdayaan Masyarakat dan Pemerintahan Desa (BPMPD) inincreasing the aparraturs capacity in village government, especially related tomanaging village’s fund in Sumbawa Residence. This qualitative research useddescriptive research method with inductive approach. The data gathering techniqueswere interview, moderate observation, questionnaire, and document. The researchresult was analyzed by data reduction, data display, conclusion taking, and SWOTanalysis and litmus test to determine the strategy which will be done. Based on theresearch results, it could be concluded that : 1) The aparraturs capacity in villagegovernment related to village’s fund management in Sumbawa Residence was low. 2)the strategies used by BPMPD in Sumbawa Recidence in managing the village’s fundwere : a) creating competent basis of raising village government’s aparraturs; b)giving reward and punishment; c) conducting cooperation and coordination withgovernment from other residences through sharing budget; d) conducting founding andevaluation of village government’s aparraturs performance. The recommendationwhich was given based on the research result was paying and giving attention to thestrategies based on those research results as the strategies to increase the capacity ofvillage government’s aparraturs by BPMPD in Sumbawa Residence.